2016
DOI: 10.1530/erc-16-0122
|View full text |Cite
|
Sign up to set email alerts
|

PYK2 via S6K1 regulates the function of androgen receptors and the growth of prostate cancer cells

Abstract: Androgen receptor (AR) is a steroid hormone receptor that functions as a transcription factor for regulating cell growth and survival. Aberrant AR function becomes a risk factor for promoting the progression of prostate cancer (PCa). In this study, we examined the roles of proline-rich tyrosine kinase 2 (PYK2) and ribosomal S6 kinase 1 (S6K1) in regulating AR expression and activity and growth properties in PCa cells. Compared with normal prostate tissues, PCa tumors exhibited high levels of PYK2 and S6K1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Pyk2 is a critical component of Ca 2+ -induced signaling pathways controlling cell survival in lung cancer ( 66 ), Src activation and metastasis in breast cancer ( 41 ), and in neuroprotection through the Pyk2/ERK/CREB pathway ( 84 ). The role of Pyk2 in the survival and proliferation of cancer cells is established ( 31 , 43 , 66 , 80 , 85 , 88 ). The work here confirms the importance of calcium influx through TRPM2 in activation of Pyk2 and modulation of cell viability in cancer ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyk2 is a critical component of Ca 2+ -induced signaling pathways controlling cell survival in lung cancer ( 66 ), Src activation and metastasis in breast cancer ( 41 ), and in neuroprotection through the Pyk2/ERK/CREB pathway ( 84 ). The role of Pyk2 in the survival and proliferation of cancer cells is established ( 31 , 43 , 66 , 80 , 85 , 88 ). The work here confirms the importance of calcium influx through TRPM2 in activation of Pyk2 and modulation of cell viability in cancer ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonreceptor proline-rich tyrosine kinase 2 (Pyk2) is an important signaling molecule that senses changes in intracellular calcium levels and translates them into alterations in cell function. Pyk2 is overexpressed in many cancers ( 43 ) and Pyk2 inhibition attenuated survival and proliferation of small cell lung cancer ( 66 ), breast cancer ( 80 ), ovarian clear cell cancer ( 85 ), multiple myeloma ( 88 ), and prostate cancer ( 31 ). Ca 2+ influx through TRPM2 can activate Pyk2 and amplify ERK signaling in U937 cells.…”
Section: Introductionmentioning
confidence: 99%
“…As another example, E2 signaling also occurs through the N-terminal truncated ERα isoform, or the orphan nuclear ER-related receptor α (ERRα) which is differentially expressed relative to ERα and ERβ in OBs and was reported to affect bone formation (Bonnelye and Aubin, 2002,Parikka et al, 2005,Bonnelye et al, 2001). In addition, a recent study found that Pyk2 promoted the expression and phosphorylation of the androgen receptor (Hsiao et al, 2016), suggesting a possible altered signaling of the androgen receptor in Pyk2-KO OBs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PYK2 modulates the signaling of androgen receptors and thus promotes growth of prostate cancer cells. 34 In breast cancer cells, PYK2 functions by integrating growth factor and cytokine receptors signaling. 35 Besides membrane receptors, PYK2 can also sustain endosomal-derived receptor signaling and enhance epithelial-to-mesenchymal transition of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%